PATH-13. SEX-LINKED TUMORAL MGMT STATUS AND OUTCOMES IN NEWLY DIAGNOSED GLIOBLASTOMA. (11th November 2019) - Barnett, Addison; Saeed Bamashmos, Anas; Ali, Assad; Li, Hong; Bosler, David; Lathia, Justin; Yeaney, Gabrielle; Sagar, Soumya; Yu, Jennifer; Murphy, Erin; Chao, Samuel; Suh, John; et al.
Abstract: INTRO/OBJECTIVE: Glioblastoma (GBM) and MGMT have been reported to have sexual dimorphism. The primary objective of this study was to analyze the impact and association between sex and MGMT status on progression-free survival (PFS) and overall survival (OS) in patients with newly diagnosed GBM. METHODS: 582 patients with newly diagnosed GBM who underwent first surgical intervention at a single tertiary care institution between 2012 and 2018 were reviewed. Adults with documented methylated (≥ 12) and un-methylated (≤ 7) MGMT status were included. A Kaplan-Meier and Cox proportional hazard models were used to analyze the association between sex and MGMT status on PFS and OS. RESULTS: 464 adult patients (median age 63.4, 36.6% female) had documented MGMT status. Overall rate of MGMT methylated patients was 42.5%, while females were more often methylated than males (52.1% vs 37.4%, p=0.004). MGMT methylated compared to un-methylated females (median: 12.8 vs 7.4 months; 1-yr: 53% vs 27%) had a greater PFS benefit than males (median: 9.6 vs 6.8 months; 1-yr: 44% vs 23%). OS was significantly improved in MGMT methylated compared to un-methylated patients among females (p=0.001) but not among males (p=0.22). Among MGMT methylated patients, females had significantly better OS compared to males (median: 18.7 vs 12.4 months; 2-yr OS: 36.8% vs 24.3%, p=0.03). Although statistically not significant, a similar pattern was observed on PFS (median: 12.8 vs 9.6 months; 1-yr PFS: 52.6% vs 44.4%). Compared to MGMT methylated females, MGMT methylated males had a PFS HR=1.22 (95% CI=0.80 – 1.85, p=0.36), and an OS HR=1.45 (95% CI=1.03 – 2.04, p=0.032). CONCLUSION: MGMT methylation is more common in females and methylation had a larger impact on both PFS and OS in females compared to males. These analyses highlight the need to further investigate sex differences that can inform clinical management of GBM.